Factors Associated with Abdominal Obesity in the Productive Age in Surabaya - Fani Kusteviani (Universitas Airlangga, 2015)
Obesity has become a public health and nutrition issues the world both developed countries and developing countries, including Indonesia. Abdominal obesity is one type of obesity where there is abdominal fat deposits as measured by waist circumference. Abdominal obesity is more at risk of health problems such as diabetes mellitus, metabolic syndrome, hypertension and cardiovascular disease than general obesity. Behavioral and environmental factors as well as genetic plays a role in the onset of abdominal obesity. The purpose of the study was to analyze factors associated with abdominal obesity in the productive age (15-64 years) in Surabaya. The independent variables used were age, sex, marital status, family size, education, occupation, smoking, physical activity, consumption of vegetables and or fruit, food or sugary drinks, fatty foods and mental health. This research was analytical study use cross sectional design. The study used secondary data from Basic Health Research Surabaya 2007 amounted to 2191 respondents by simple random sampling. Data were analyzed with Chi-square test and logistic regression. Result of analysis showed that risk factors of abdominal obesity were age 35-64 years, female gender and married or divorced status, level of education ≤ SMA and consume fatty food regularly. The most influential risk factors are female. Increasing knowledge, physical activity, and reducing fat intake can prevent the risk of abdominal obesity. Keyword: abdominal obesity, productive age, lifestyle, female